2011
DOI: 10.1038/onc.2011.163
|View full text |Cite
|
Sign up to set email alerts
|

GLI1-dependent transcriptional repression of CYLD in basal cell carcinoma

Abstract: CYLD is a deubiquitination enzyme that regulates different cellular processes, such as cell proliferation and cell survival. Mutation and loss of heterozygosity of the CYLD gene causes development of cylindromatosis, a benign tumour originating from the skin. Our study shows that CYLD expression is dramatically downregulated in basal cell carcinoma (BCC), the most common cancer in humans. Reduced CYLD expression in basal cell carcinoma was mediated by GLI1-dependent activation of the transcriptional repressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
(31 reference statements)
1
28
0
Order By: Relevance
“…10). Previous studies have reported that SNAI1 is required for cell proliferation in malignant melanoma (57,58) and ZEB1 induces proliferation and tube formation through upregulation of VEGF in human umbilical vein endothelial cells (59). It has also been reported that SNAI and ZEB family members inhibit cell cycle progression, resulting in accumulation of cells in G1 phase of cell cycle in epidermoid A431 cells (60).…”
Section: Discussionmentioning
confidence: 99%
“…10). Previous studies have reported that SNAI1 is required for cell proliferation in malignant melanoma (57,58) and ZEB1 induces proliferation and tube formation through upregulation of VEGF in human umbilical vein endothelial cells (59). It has also been reported that SNAI and ZEB family members inhibit cell cycle progression, resulting in accumulation of cells in G1 phase of cell cycle in epidermoid A431 cells (60).…”
Section: Discussionmentioning
confidence: 99%
“…This is deemed to be due to CYLD’s role in checking inflammation which has been demonstrated in many types of cancer [17, 18, 34, 35, 5760]. Since NF-kB-mediated inflammation is widely known to cause the generation of tissue damaging reactive oxygen species, inflammatory cytokine cascades and recruitment of immune cells (which release factors like granzymes and superoxides), it is logical that CYLD’s ability to cut off NF-kB activation would limit subsequent damage.…”
Section: Cyld Overviewmentioning
confidence: 99%
“…RhoA, in particular, was found to be controlled by CYLD through action on LARG (Leukemia Associate RhoGEF) [86]. Basal cell carcinoma, one of the most common cancers in humans, was shown to downregulate CYLD transcript by the action of the Snail transcription factor, which is in turn activated by the Kruppel zinc finger gene GLI1 [32, 35]. This downregulation affected the keratinocyte cancer cells by increasing their proliferation, which could no longer be controlled by CYLD.…”
Section: Cyld Functionmentioning
confidence: 99%
“…Furthermore, inhibition of the dysregulated tropomyosin kinase TRK has also been proposed as a strategy to treat tumors with loss of CYLD (Rajan et al, 2011). In a different approach, it has been recently suggested that downregulation of Snail (a CYLD repressor) through inhibition of its activator GLI1 could reverse the dramatically reduced expression of CYLD in basal cell carcinomas (Kuphal et al, 2011). Finally, exploiting concepts such as synthetic lethality could facilitate the identification of novel therapeutic targets in the DUB family.…”
Section: Targeting Dubs In Cancermentioning
confidence: 99%